Analisis Pengaruh Penerapan Good Corporate Governance Terhadap Pertumbuhan Modal Koperasi - carmidah carmidah (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2020)
The purpose of this reseach is to analyze whether the application of corporate governance principles have an influence on the performance of Cooperatives. This study was conducted on 132 Cooperatives which reported the financial reports of 2015 until 2016 to Department of Industry, Commerce, and Cooperatives of Pemalang District (DESPERINDAGKOP). The approach used was a purposive sampling. The collected data was then analyzed using multiple regressions. The result of this reseach showed that transparency, accountability, independence and fairness partially have a significant positive effect on capital growth, while responsibility does not have it. The obstacles found in this study were the financial reports which were used in only two years. Therefore, it presents far less accurate figure in relation with the performance measurement of cooperatives.